2021
DOI: 10.3390/su13137124
|View full text |Cite
|
Sign up to set email alerts
|

Rangeland Biodiversity and Climate Variability: Supporting the Need for Flexible Grazing Management

Abstract: Resting or grazing exclusion is an effective practice widely adopted to restore degraded, arid rangelands. To understand its effect on plant diversity, we studied Hill’s diversity indices during two growing seasons (2017–2019). The experiment consisted of a three-level factorial design with four plant communities subjected to different resting durations (one, two, and three years) compared to continuously grazed areas (control). The results showed that rainfall plays an important role in arid rangeland restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Therefore, it is important to base grazing plans on the state of the vegetation cover rather than simply on the length of resting times. This result supports findings highlighting the need for flexible grazing management depending on weather and climate variability (Louhaichi et al, 2021a) and offers an opportunity to develop grazing strategies that exploit these results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, it is important to base grazing plans on the state of the vegetation cover rather than simply on the length of resting times. This result supports findings highlighting the need for flexible grazing management depending on weather and climate variability (Louhaichi et al, 2021a) and offers an opportunity to develop grazing strategies that exploit these results.…”
Section: Discussionsupporting
confidence: 87%
“…Rangeland management strategies can be used as a tool to improve sustainability (Louhaichi et al, 2019(Louhaichi et al, , 2021a. A growing number of studies have shown the positive contributions of grazing and how it can be a cost-effective practice for enhancing productivity, species diversity, and ecosystem health (Hodgson et al, 2005;Dorrough et al, 2007;Kohyani et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Its blooming phase begins in late winter [4]. Southern Tunisia has an arid Mediterranean climate with a long-term annual rainfall of 80 mm concentrated in the growing season between September and April and a dry season lasting about 4 months from May to August [5]. It was previously reported that the content of secondary plant metabolites is not stable and depends on the growth stage, the part of the plant and the characteristics of the environment.…”
Section: Introductionmentioning
confidence: 99%